Possibility of development wine tourism in Serbia - Milić, Dušan; Riste, Elenov; Jovana, Draginčić (Economics of Agriculture, 2010)
Viticulture and Enology as an inseparable companion of this production are of great importance from the point of rational exploitation of land, employment of the population, the possibility of achieving a satisfactory income, realization on the domestic and foreign markets, the development of tourism and the like. Wine route or wine tourism is a specifc form of tourism, which combines wine tasting of a particular wine-growing region with natural beauty, customs, and cultural – historical monuments of the area. The development of wine tourism could bring many benefts, to both caterers and wine producers, and could contribute to the improvement of the wine quality in Serbia. It can also provide creative and quick revival and improvement of the tourist offer. Wine tourism could soon become one of the Serbian brands. Opening the "wine routes" through Serbia is a very serious and responsible work that exceeds the capabilities of an individual. The state is prepared to subsidize this form of tourism, and tourism organizations are preparing "wine maps" that will help guests to get acquainted with the eight regions in Serbia where the highest quality wine is produced. These are the wine routes of Palić, Fruška Gora, Vršac, Smederevo, Topola, Negotin, Knjaževac and Župa.